Developing Strategies to Enhance Employee Retention at Assumption Learning Loft, Myanmar - William; Fernando, Maria Socorro (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
In many industries, especially education institutions operating in politically and economically unstable environments like Myanmar, employee retention is still a major concern. This study what makes Assumption Learning Loft (ALL), Myanmar an employer of choice for training centers that struggle to keep teachers on staff even with their competitive pay, great professional development possibilities, and first-rate facilities. To investigate important retention elements Interpersonal Relationships, Career Development, Perceived Organizational Support, and Employee Retention, in-depth interview with eight employees were done using a qualitative research approach based on the Appreciative Inquiry (AI) model. Numerous factors, including economic instability, rivalry from newly established private schools, and the allure of chances overseas, were found to have an impact on retention. It is recommended that a positive workplace culture be fostered by implementing a mutual respect culture and a recognition and reward system; that professional growth be supported by establishing clear career pathways and enhancing regular training programs; and that competitive compensation be ensured by conducting structured salary reviews. Crucial tactics to increase retention were also emphasized, like fortifying open lines of communication and establishing clear promotion and compensation guidelines. These findings give practical methods to improve staff stability and organizational productivity in difficult conditions, and they offer a valuable framework for Assumption Learning Loft (ALL) and other educational institutions facing comparable issues.